Variation in arterial supply of human vermiform appendix - M, Janardhana Rao; Mohammad, Reshma (International Journal of Research in Medical Sciences, 2017)
Precise knowledge of vascular variation and planning of conducting surgical and radiological procedures is important during appendectomy. During the routine medical undergraduate educational dissection of 63 year old male cadaver we found appendicular artery (AA) a branch of the inferior division of the ileocolic artery (ICA). The AA passed in front of the terminal part of the ileum, and entered the mesoappendix of the vermiform appendix. It runs near the free margin of the mesoappendix and ends in branches which supplied the appendix. The reminding of this type of variation is also important while performing the surgeries or dissections.